Tapered dielectric quad-cavity MOSHEMT: a double-gate design for enhanced biosensing - Dastidar, Ananya; AbdelAll, Naglaa; Patra, Tapas Kumar; Mohapatra, S. K.; Pradhan, K. P.; Khouqeer, Ghada A. (Frontiers in Physics, 2026)
Rapid and accurate biomolecule detection is vital for next-generation diagnostic and sensing technologies. Reliable biosensing has driven innovations in transistor-based detection platforms. In this work, a quad-cavity double-gate tapered dielectric metal oxide-semiconductor high electron mobility transistor (MOSHEMT) is investigated using technology computer-assisted design (TCAD) simulations for biosensing applications. The proposed structure leverages dielectric modulation and taper cavity geometry to improve electrostatic control and charge sensitivity. Comparative analysis with conventional architectures, including single-gate single-cavity, single-gate dual-cavity, and double-gate non-tapered quad-cavity MOSHEMTs, demonstrates improvements of 54%, 25%, and 84% in drain current sensitivity, respectively. Parametric variation of the taper angle reveals that 60° provides optimal sensitivity due to the enlarged effective surface area for biomolecule binding. Moreover, the device maintains reliable detection capability for biomolecule fill factors as low as 15%, indicating its suitability for low-concentration biosensing environments.